Investigating mental health service user views regarding sexual and relationship issues - McCann, Edward (My University, 2010)
To date, very few empirical studies exist that investigate sexual and relationship issues and people who experience enduring mental health problems and less attention has been paid to the personal accounts of clients in this respect. The present study, carried out in the UK, involved 30 people who were asked about past and present relationship experiences and elicited hopes and aspirations for future sexual and relationship needs. A semi-structured interview schedule was constructed that specifically addressed potential sexual and relationship concerns and was conducted face-to-face. The aim was to capture in-depth perspectives of people with a medical diagnosis of schizophrenia regarding intimate relationships. The results of the study showed that people are willing and able to articulate thoughts, feeling and beliefs in the area. The findings are presented, and the implications in terms of mental health practice, education and research are discussed.
PUBLISHED
Keywords: psychosis; mental health; relationships; sexuality; schizophrenia; service user views; service users; sexuality; Ageing; Identities in Transformation; Inclusive Society